Nogi. Męskość i niepełnosprawność w Szpitalu Czerwonego Krzyża Michała Choromańskiego - Galant, Arleta (Przestrzenie Teorii, 2020)
In the article, the author presents an interpretation of the novel Szpital Czerwonego Krzyża by Michał Choromański. One of the key interpretative hypothesis advanced by the author of the article based on a reading of the novel is the assumption that the work constitutes an important statement on masculinity and disability, exposing the artificiality and unoriginality of masculine gender roles and criticizing somatic culture. This criticism is, in turn, significant with regard to twentieth-century reflections on body issues in post-war modernity. The author of the article indicates that Choromański’s work, written before the Second World War but published not until 1956, is a piece of significance for the reconstruction of issues of disability in terms of Polish literary history.